PENGARUH JENJANG PENDIDIKAN, UKURAN USAHA, LAMA USAHA DAN LATAR BELAKANG PENDIDIKAN ATAS PENGGUNAAN INFORMASI AKUNTANSI TERHADAP KEBERHASILAN USAHA (Studi Kasus pada UKM di PIK Pulogadung) - Hj. Dewi Rejeki, SE., Ak., M.Ak.; Irma Julyanda (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
One of the main factors that cause problems and lead to the failure of micro, small and medium enterprises (SMEs ) in developing businesses is the lack of ability in using accounting information . The purpose of this study was to determine the effect of education , size of business , length of business and educational background on the use of financial information to the success of SMEs . This research is expected to provide empirical evidence of the use of information on SMEs which are partners of the PIK Pulogadung in East Jakarta area. The population in this study are all small and medium entrepreneurs in PIK Pulogadung listed as UPK PPUMKM Pulogadung totaling 42 employers . The data collection was conducted by field surveys using a questionnaire. Methods of data analysis using descriptive analysis and multiple regression analysis with α 0:05 . The results showed levels of education, size of business , and educational background does not significantly influence the success of the business . While the old variable effort significantly affect business success variables . Suggestions for the company SME , companies need to better understand the use of accounting information of SMEs , companies must better understand and use accounting information as information operations , management accounting information and its specialty for financial accounting information more attention again , the provision of financial statements absolutely must be provided when SMEs need capital and will be applying for a loan to the Bank .